President’s Message: Endings and Beginnings - Knight, Mary (Operating Room Nurses Association of Canada Journal, 2001)
ORNAC has reached another milestone. 0 Our Editor, Agnes Forster and our Publisher, Ron Forster will be retired by the time you are reading this. We have come a long way together since the first issue was published in February 1983. With their retirement, Ron and Agnes have turned the Journal over to ORNAC, and I would like to express our heartfelt appreciation. Best wishes for a happy retirement!